Analysis of the agricultural productivity of the sugarcane crop in regions of new agricultural expansions of sugarcane - Bernardo, Roberto; Lourenzani, Wagner Luiz; Satolo, Eduardo Guilherme; Caldas, Marcellus Marques (Universidade Federal de São Carlos, 2019)
Abstract The launching of biofuel vehicles in 2003 led to ethanol demand increase and a new phase of expansion of sugarcane cultivation in Brazil. Although the increase in area of production and the quantity of sugarcane produced have been very important to Brazilian agribusiness, the recent agricultural productivity rate has slowed. In this context, this article analyzed the factors that influence the growth rate of sugarcane productivity in the regions of new agricultural expansions, specifically in the states of Mato Grosso do Sul and Goias. For the collection and data analysis, we used bibliographical and documentary research. The shift-share method was used to analyze the evolution of sugarcane production, through the decomposition of this variable into two factors: area effect and productivity effect. The results show that the increase in production in the region under analysis was mainly due to the incorporation of new planting areas and not to an increase in productivity. In addition, structural factors have negatively impacted crop performance. The analysis indicates that there is a slow rhythm of sugarcane fields’ renovation and the adoption of old varieties. Although the mechanization index is high in the studied regions, difficulties of technological adaptation still provide deficiency in the agricultural performance of sugarcane.

Resumo O lançamento dos veículos bicombustíveis, no ano de 2003, propiciou a retomada da importância da produção de etanol e, consequentemente, numa nova fase de expansão do cultivo de cana-de-açúcar no Brasil. Embora o aumento da área de produção e da quantidade produzida de cana-de-açúcar mereça destaque no agronegócio brasileiro, o mesmo não se pode considerar para a sua produtividade agrícola recente. Nesse contexto, esse artigo analisou os fatores que influenciam o ritmo de crescimento da produtividade da cana-de-açúcar, nas regiões de novas expansões agrícolas canavieiras, especificamente, nos estados de Mato Grosso do Sul e de Goiás. Para a coleta e análise dos dados foram utilizadas a pesquisa bibliográfica e a documental. O método Shift-Share foi utilizado para analisar a evolução da produção de cana-de-açúcar, por meio da decomposição dessa variável em dois fatores, efeito área e efeito produtividade. Os resultados demonstram que o aumento da produção, na região em análise, deveu-se predominantemente à incorporação de novas áreas de plantio e não por incremento na produtividade. Além disso, fatores estruturais têm impactado negativamente no desempenho da cultura. As análises indicam que há um ritmo lento de renovação dos canaviais, com a adoção de variedades antigas. Embora o índice de mecanização nas regiões em estudo seja alto, dificuldades de adaptação tecnológica ainda proporcionam deficiências no desempenho agrícola canavieiro.
Análise da produtividade agrícola da cultura da cana-de-açúcar em regiões de novas expansões agrícolas canavieiras
Keywords: Sugar and alcohol industry; Agricultural mechanization; Shift-share; Setor sucroalcooleiro; Mecanização agrícola; Shift-share